2017
DOI: 10.1209/0295-5075/118/20002
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond PFA: A precise formula for the sphere-plate Casimir force

Abstract: -Quantum fluctuations of the electromagnetic field in the medium surrounding two discharged macroscopic polarizable bodies induce a force between the two bodies, the so called Casimir force. In the last two decades many experiments have accurately measured this force, and significant efforts are made to harness it in the actuation of micro and nano machines. The inherent many body character of the Casimir force makes its computation very difficult in nonplanar geometries, like the standard experimental sphere-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 53 publications
(125 reference statements)
3
46
0
Order By: Relevance
“…which is sufficiently precise for our purposes. As was shown recently [42][43][44], the relative correction to the proximity force approximation is approximately equal to 0.5a/R, i.e., varies from 0.19% to 0.33% when the separation increases from 235 to 400 nm. In Fig.…”
Section: The Experimental Results and Comparison With Theorysupporting
confidence: 57%
“…which is sufficiently precise for our purposes. As was shown recently [42][43][44], the relative correction to the proximity force approximation is approximately equal to 0.5a/R, i.e., varies from 0.19% to 0.33% when the separation increases from 235 to 400 nm. In Fig.…”
Section: The Experimental Results and Comparison With Theorysupporting
confidence: 57%
“…In doing so, special experimental efforts have been taken to avoid any impact of electrostatic patches on the measurement results for the Casimir force. On the theoretical side, due to the long-term efforts of several authors it was shown that the influence of deviations from the proximity force approximation [35,36], as well as the role of surface roughness [3,4,40,41], does not change the obtained results. Thus, the Casimir puzzle assumes a fundamental importance casting doubts on the basic assumption of quantum statistical physics that a material system responds similarly to electromagnetic fields with nonzero field strength and to fluctuating fields possessing zero field strength and nonzero dispersion.…”
Section: The Major Improvement As Compared To Previous Experiments mentioning
confidence: 99%
“…After the experiment [16] on measuring the difference Casimir force was performed, where the theoretical predictions of the Lifshitz theory using the Drude and plasma models differ by up to a factor of 1000, an exclusion of the former within this separation range was conclusively established. In so doing the role of different background effects, such as the surface roughness [49,50], variations in the optical data [51], patch potentials [52,53] etc., as well as the validity of calculation procedure (including the role of deviations from the proximity force approximation [54][55][56][57][58]), were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%